If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 2x = 3x + -15 Reorder the terms: 15 + 2x = -15 + 3x Solving 15 + 2x = -15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 15 + 2x + -3x = -15 + 3x + -3x Combine like terms: 2x + -3x = -1x 15 + -1x = -15 + 3x + -3x Combine like terms: 3x + -3x = 0 15 + -1x = -15 + 0 15 + -1x = -15 Add '-15' to each side of the equation. 15 + -15 + -1x = -15 + -15 Combine like terms: 15 + -15 = 0 0 + -1x = -15 + -15 -1x = -15 + -15 Combine like terms: -15 + -15 = -30 -1x = -30 Divide each side by '-1'. x = 30 Simplifying x = 30
| 5(3y-1)=-35 | | 2(w+1)+4w=3(2w-1) | | 25z^2-36=0 | | 2(n+6)=36 | | 2x-5=3x+21 | | 14z-(3z-2)=[5z+2-(2-1)] | | 2p^2=-13p-15 | | 3(y-2)-4y=2(y-9) | | y=-2+.3+5 | | -9v+1=-80 | | 16x^2-a^2=0 | | 7x+4+5x=148 | | (4x-11)+x=204 | | 20x^2=-15x | | n-10+10=30 | | 4y^2-12=0 | | (3x^2y)-(-2x)(xy^2)=n | | -3(v+5)+2=4(v+2) | | -6(4y-8z)+8(3y-6z)= | | 3(w+2)-w=2(w-1)+5 | | -17=-17z | | x^2-20-x=0 | | 4t+8-6= | | 9(8n-4n)= | | .5t+.25(t+16)=4+.75t | | 2x^2+9x-126=0 | | 2a=5a+12 | | (xy-2(x))-3y+12=0 | | -5(8m-4n+6)+6(9m+7)= | | 4(w-3)-6w=-2(w+6) | | h^2+15+16h=0 | | S=1(n-2) |